Symmetry in triple hop distance hides asymmetries in knee function after ACL reconstruction in athletes at return to sports - Kotsifaki, A.; Van Rossom, S.; Whiteley, R.; Korakakis, V.; Bahr, R.; Sideris, V.; Smith, P. G.; Jonkers, I. (The American Journal of Sports Medicine, 2021)
Background: After anterior cruciate ligament reconstruction (ACLR), a battery of strength and hop tests is frequently used to determine the readiness of an athlete to successfully return to sports. However, the anterior cruciate ligament reinjury rate remains alarmingly high.